313. Outpatient Treatment and Recurrence of Prosthetic Joint Infection (PJI) in Infectious Disease (ID) Physician Office Infusion Centers (POICs): A 2-Year Retrospective Multicenter Analysis. (26th November 2018) - Metzger, Brian S; Adams, John S; Bernett, Jorge R; Mandel, Richard M; Prokesch, Richard C; Lo, Carson T; Hardin, Thomas C; Schroeder, Claudia P; Van Anglen, Lucinda J
Abstract: Background: A significant complication of prosthetic joint replacement is the development of a PJI. Therapy includes prolonged IV antibiotics (IVAB), usually delivered in the outpatient setting. Follow-up (FU) in this population can be difficult, particularly for the treating ID physician. We report our experience treating PJI in an ID POIC. Methods: Retrospective chart review was conducted of patients (patients) with initial knee or hip PJI, who received ≥3 days of IVAB in 14 ID POICs from July 2015 to July 2017. Initial clinical success (ICS) was defined as no evidence of infection at the completion of outpatient parenteral antimicrobial therapy (OPAT), although continued oral antibiotics were allowed. Available FU patients were assessed at 6 months for recurrence and associated factors analyzed using χ 2 and Fisher's exact test. Results: We evaluated 171 patients (122 knees, 49 hips) with a median age of 65 years (range 31–91) and 64% male. Infection occurred within 90 days of the implant in 40% (25% within 30 days). Prostheses were retained in 109 patients (64%). 91% were hospitalized prior to OPAT for 4.7 median days, with the remainder treated from the community. The median length of OPAT was 37 days (range: 8–77). Cultures were positive in 154 patients with 122 Staphylococcus spp. pathogens (43% MSSA, 43% CoNS, 13% MRSA) in 112 patients. Most commonly prescribed IVABs were vancomycin (41%) and cefazolin (37%). ICS was achieved in 163 patients (95%), independent of prosthesis removal, with 119 (73%) continuing oral antibiotics post OPAT. Eight patients did not complete OPAT. Six-month FU to the ID physician was available for 97/163 patients completing therapy (60%). Of these, recurrence occurred in 22 patients (23%) at a median of 2.1 months (range 0.2–6). Risk factors for recurrence are noted below. Oral rifampin use with IVAB was associated with a significantly lower rate of recurrence in patients with staphylococcal PJI ( P = 0.004). Conclusion: This real-world evaluation underscores the challenges of successful treatment of PJI. ICS was readily achieved (95%). High recurrence (23%) may be exaggerated by lower likelihood of FU in asymptomatic patients. Lack of improvement in 6-month cure with prosthesis removal merits additional inquiry. Although the group was small, adjunctive rifampin suggests improved outcomes in staphylococcal PJI. Disclosures: B. S. Metzger, Allergan: Speaker's Bureau, Speaker honorarium. L. J. Van Anglen, Merck & Co.: Investigator, Research grant.